Two rare cases of appendiceal collision tumours involving an appendiceal mucinous neoplasm and carcinoid. (1st February 2016) - Tan, Hwee Leong; Tan, Grace Hwei Ching; Teo, Melissa
Abstract : We report two rare cases of appendiceal collision tumours, each involving an appendiceal mucinous neoplasm with a concomitant appendiceal carcinoid. The first case presented with acute appendicitis while the second presented with an incidental radiological finding of an enlarged appendix as part of evaluation for raised serum carcinoembryonic antigen. Diagnosis in both cases was made postoperatively on histological assessment following appendicectomy. Clinical and histological features of both tumour types in each case did not necessitate further surgical resection or adjuvant treatment. Both patients did well postoperatively and had no evidence of disease recurrence on follow-up.